Utilizing Blockchain and IoT in Food Network: Systematic Literature Review - Tocklin, Tommi (My University, 2021)
Food is required by everyone daily and because of this various supply chains have to operate smoothly to deliver quality goods to nearby stores. These operations contain several different parties and each one of them performs critical tasks. These supply networks can become very complex and their management can be a hassle. This complexity creates several challenges that could be solved with a single common platform that everyone involved uses. This approach, however, would be flawed with a centralized solution, so we need to turn into decentralized solutions like distributed ledgers. Currently consumers do not know much about the food products that they buy and eat. The goal in this thesis is to research how using blockchain technology could improve food supply chains since they face several issues currently and anything that can solve or even alleviate those would over time have a big positive impact. Currently the exact origins of products are mostly unknown due to lack of transparency and lots of food is wasted and thrown away due to various reasons which is not sustainable. Technology can provide new solutions for these issues which also involves IoT devices. Combining blockchain and IoT together can provide much safer and more transparent food supply chains for the masses. There are also several other related issues with food that could be improved, including supply chain optimization, collaboration and better data sharing. The used research method in this thesis is Kitchenham's systematic literature review. The results in this thesis cover extensively how distributed systems can benefit the parties involved in the food value chain and how these could be utilized for several things. Some potential concerns with the performance of these distributed systems and their security are also discussed.
Keywords: Blockchain,DLT,Distributed Ledger Technology,IoT,Internet of Things,food,supply chain,distributed systems